Myokine Responses to Exercise in a Rat Model of Low/High Adaptive Potential - Farrash, Wesam F.; Phillips, Bethan E.; Britton, Steven L.; Qi, Nathan; Koch, Lauren G.; Wilkinson, Daniel J.; Smith, Ken; Atherton, Philip J. (Frontiers in Endocrinology, 2021)
Introduction: Assuming myokines underlie some of the health benefits of exercise, we hypothesised that ‘high responder trainer’ (HRT) rats would exhibit distinct myokine profiles to ‘low responder trainers’ (LRT), reflecting distinct health and adaptive traits. Methods: Blood was collected from LRT and HRT (N=8) rats at baseline (BL), immediately (0h), 1h, and 3h after running; repeated after 3-wks training. Myokines were analysed by ELISA (i.e. BDNF/Fractalkine/SPARC/Irisin/FGF21/Musclin/IL-6). Results: At baseline, Musclin (LRT: 84±24 vs HRT: 26±3 pg/ml, P=0.05) and FGF21 (LRT: 133±34 vs HRT: 63.5±13 pg/ml, P=0.08) were higher in LRT than HRT. Training increased Musclin in HRT (26±3 to 54±9 pg/ml, P<0.05) and decreased FGF21 in LRT (133±34 to 60±28 pg/ml, P<0.05). Training increased SPARC (LRT: 0.8±0.1 to 2.1±0.6 ng/ml, P<0.05; HRT: 0.7±0.06 to 1.8±0.3 ng/ml, P=0.06) and Irisin (LRT 0.62±0.1 to 2.6±0.4 ng/ml, P<0.01; HRT 0.53±0.1 to 2.8±0.7 ng/ml, P<0.01) while decreasing BDNF (LRT: 2747±293 to 1081±330 pg/ml, P<0.01; HRT: 1976±328 to 797±160 pg/ml, P<0.05). Acute exercise response of Musclin (AUC) was higher in LRT vs HRT (306±74 vs. 88±12 pg/ml×3h-1, P<0.01) and elevated in HRT after training (221±31 pg/ml×3h-1, P<0.01). Training elevated SPARC (LRT: 2.4±0.1 to 7.7±1.3 ng/ml×3h-1, P<0.05; HRT: 2.5±0.13 to 11.2±2.2 ng/ml×3h-1, P<0.001) and Irisin (LRT: 1.34±0.3 to 9.6±1.7 ng/ml×3h-1, P<0.001; HRT: 1.5±0.5 to 12.1±1.9 ng/ml×3h-1, P<0.0001). Conclusion: Exercise training alters how myokines are secreted in response to acute exercise. Myokine responses were not robustly linked to adaptive potential in aerobic capacity, making them an unlikely regulator of adaptive traits.